شرح ابن الأنصاري لمنفرجة التوزري - أندم, عبد السلام محمد (Sharwes Scientific Journal, 2024)
The poem (Al-Munfarajah) composed by Youssef bin Muhammad Al-Tawzari is one of the most famous Sufi poems that are abundant in the Arab-Islamic heritage. Its fame lies in being a prominent example of poems of supplication and seeking relief from God Almighty in times of hardship and tribulation. Its fame spread among the people in the East and West of the earth, and those interested sang it in the gatherings of remembrance, and the pens of writers and historians recorded it, and generations passed it down. Its fame reached the point that it was translated into other languages, such as Turkish and Persian, and scholars from most regions and regions rushed to explain it and decipher its symbols, and among them is Ibn Al-Ansari, so how did he deal with it? And was he good in his explanation of it, and was he successful in his dealing with it? And how does he distinguish himself from other commentators?   Ibn Al-Ansari is one of the brilliant linguists who studied the poem (Al-Munfarajah) in depth, breadth, and detail through his scientific work entitled (Al-Adwaa Al-Bahjah fi Ibriz Daqaiq Al-Munfarajah), which gave it a wide-ranging fame, and distinguished the methodology and results of its author from his peers and contemporaries.   We will approach this topic using the descriptive analytical approach, and compare it with his predecessors and contemporaries. We will also employ a group of authentic linguistic standards and interpretations, and present the conclusions and inferences, and the intended grammatical purposes and outlooks.   Ibn Al-Ansari's explanation of Al-Munfarajah is characterized by diversity and breadth, and the solid and solid presentation of linguistic issues and the rules of Arabic grammar and prosody, and the elaboration in interpreting the pillars and issues of rhetoric, discourse, and stylistics nested in the poem. The commentator also balances between the versions, identifies the notables, makes useful and successful additions, and comments on what was missed by the brilliant early commentators. Ibn Al-Ansari is not a mere transmitter of the opinions of his predecessors. He read, understood, refined, arranged, simplified, and abbreviated the studied work according to the context or the requirements of the situation, which made him accomplish a comprehensive linguistic explanation, containing within its folds every interesting and charming science, and showing that he was indeed a unique linguist; broad in culture and insight, open-minded, and firmly rooted in methodology and specialization. The man was a sea well-versed in various sciences. One study counted sixty-three different works of his in jurisprudence, readings, hadith, language, literature, interpretation, philosophy, and other various sciences. He was not arbitrary in his criticism, or biased towards anyone. In his writings, he addressed the shortcomings of expressions, filled the gaps, and made up for what his predecessors missed